ADDITION OF PET POWDER TO REPLACE FINE AGGREGATE IN INTERLOCKING FLOORS - Barreto, Kleyton (Journal of Interdisciplinary Debates, 2023)
The growing quest to reduce the impacts generated on the environment, the application of materials of alternative origin in civil construction increases and the need for companies to reduce costs through the recycling of materials that would be disposed of in the trash. One of these materials is PET (polyethylene terephthalate), a material with certain resistance and flexibility. This study envisages analyzing the tensile strength of concrete when incorporated with fiber or PET bottle powder as an addition, verifying the feasibility of this union.